(untitled) (Journal of Pharma Insights and Research, 2023)
The objective of present study was an attempt to formulate and evaluate delayed release orally disintegrating tablets for Lansoprazole, which is a benzimidazole anti-ulcer agent and is one of the most widely, used drugs for treating mild and severe ulcers. Successful delivery of drugs specifically to the intestine requires the protection of drug from being release in stomach. The present study demonstrates that the lansoprazole enteric-coated granules could be successfully intestine targeted by using pH dependent polymers in different concentrations. By observing the dissolution profile for all the formulations F5c was better formulation of all the formulation. Formulation F5c was formulated as lansoprazole delayed release orally disintegrating tablets by using HPMC E5, Eudragit L30 D-55 and Eudragit NE 30D. Formulated tablets showed delayed in vitro dissolution behavior, probably due to optimized concentration of polymers. The value of regression correlation coefficient (R2) was calculated for all the formulations F1-F8 that values were close to 1. Among regression correlation coefficient (R2) values of Higuchi’s equation, Korsmeyer-Peppas equation and Hixson-Crowell equation, R2 values of Korsmeyer-Peppas equation was found to be higher and the n values was found to be (n<0.45) release mechanism. Similarly, between Zero order and First order equation, R2 values of zero order equation was found to be higher. Hence, the drug release followed zero order release kinetics with fickian diffusion mechanism. The optimized formulation F5c was stable at 25°C/60% RH and 40°C/75% RH as per ICH guidelines, after 2 months.